Pharmacologically targeting Schwann cells to improve regeneration following nerve damage - Alhamdi, Alaa A.; Mackie, Shona; Trueman, Ryan P.; Rayner, Melissa L. D. (Frontiers in Cell and Developmental Biology, 2025)
Schwann cells provide essential support for nerve growth and survival following peripheral nerve damage by producing various growth factors and other signalling molecules. Modulating the proliferation, differentiation, migration, or myelination of Schwann cells could result in accelerated repair and regeneration of injured nerves, ultimately leading to improved motor and sensory function. Therefore, Schwann cells are commonly advocated as therapeutic targets for nerve damage, which could be mediated by pharmacological intervention. This review discusses how compounds such as growth factors, hormones, and small molecules can regulate intracellular signalling pathways involved in modulating Schwann cells.